APLIKASI INVENTORY PADA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS BENGKULU - Hayadi, B Herawan; Hermawansyah, Hermawansyah (UNIVED Press, 2012)
The development of information technology has influenced many aspects of life and profession, it causes changing system toward the institute or company, it also changes their working system in order to make more effective and efficient. The tendency demands people to be more active in improving the professionalism in work especially the ability of goods inventory operator in data collecting, checking and evaluating unmovable goods inventory collection of state owned in order to be highly structured. This research was aimed to make a system that can give information about the data of goods inventory of the Teacher Training and Education Faculty of Bengkulu University. By using application of goods inventory be intended to make easier in making the informative report and the increasing of staff’s efficiency in fieldwork of the Teacher training and Education Faculty of Bengkulu University. The conclusion of the research was the assembling of this application is very important to facilitate of administration work in company or government instance especially in of goods inventory collection of state owned.